Variation in the shell elements of Chrysemys picta bellii (Gray 1831) - Corsini, Joseph (Vertebrate Anatomy Morphology Palaeontology, 2023)
Variation in the Shell Elements of Chrysemys picta bellii (Gray 1831) Assignment of fossil turtle shell elements to a specific taxon is often difficult because the range of variation within the population is usually not well characterized. In addition, it is sometimes not clear whether the fossil forms actually differ from their extant counterparts because often the range of shell element variation in modern species has not been determined. The emydid turtles are no exception, with confusion often arising in the identification of isolated fossil elements and sometimes intact shells representing Emys, Pseudemys, Malaclemys, and Graptemys, as well as the deirochelyids Chrysemys, Clemmys, Deirochelys, and Trachemys. In order to begin providing a database with modern counterparts of the deirochelyid turtles, I have photographed and illustrated seven extant Chrysemys picta bellii shells, six of which were collected at a single pond in Nebraska and one from Ladd Marsh in Union County, Oregon . Photographs and detailed illustrations indicate a broad range in the shapes of many characters. Side by side comparisons of some key elements show that there is significant variation in several important characters (nuchal shape/sulci, entoplastron shape/sulci, and pygal shape/sulci). I also conducted a limited morphometric analysis of several sulcus/suture distance ratios, showing substantial variation between individuals in some cases. Covariance and correlation analysis of this variation suggests that allometry is not involved in most cases. In summary, this work provides a visual and morphometric dataset for aid in identifying and assigning shell elements of fossil emydid turtles.